Asymmetric Methods for Carbon‐Fluorine Bond Formation. Issue 44 (2nd November 2021) - Remete, Attila M.; Nonn, Melinda; Escorihuela, Jorge; Fustero, Santos; Kiss, Loránd
Abstract: As a consequence of the ever‐increasing relevance of fluorinated drugs in medicinal chemistry, organofluorine chemistry has become a hot topic research area during the last decade. Asymmetric carbon‐fluorine bond‐forming reactions have enormously developed in recent years with considerable findings related to novel reactions and synthetic approaches. These new synthetic efforts have contributed to the access to a growing number of fluorinated molecules and complex natural or synthetic products of high relevance in medicinal chemistry and drug research. Illustrative examples of novel synthetic methodologies, including organocatalytic processes, asymmetric syntheses or phase‐transfer catalytic methods for the enantioselective incorporation of fluorine atom(s) into versatile molecular entities, are covered in the current Review, focusing on main contributions of the last ten years. Abstract : Some illustrative examples of novel synthetic methodologies including organocatalytic processes, asymmetric syntheses or phase‐transfer catalytic methods for the enantioselective incorporation of fluorine atom(s) into versatile molecular entities are covered in the current review, focusing on main contributions of the last decade.